Antext: a story of family firm resilience - Sousa, João Emidio Lima Baía de (2018)
The present case is based on the real story1 of the Vieira family, and describes their journey with the objective of ensuring the survival of the family textile business. It is presented through Aquiles Jr.’s perspective, heir of the firm, who struggles to save a company that is drowning in debt but whose emotional value and significance justify decisions that go beyond rationality. The main purpose of this case is to illustrate the existence of superior levels of organizational resilience in family firms, highlighting the importance of socioemotional wealth as a key driver for this resilience among several other factors, but also the complexity of the decision-making process in emotionally charged environments and the particular dynamics of a family business. A teaching note was included at the end of the case to support its utilization in a classroom environment. It includes a theoretical background and several suggested questions and answers.